Analisis Actor Network Theory Dalam Program Pusat Pembelajaran Pemberdayaan Perempuan (Putaran) di Kota Surabaya - Aliefa Rizkya Ananda; Nofiro Bening Dwi Wangkasa; Berlian Fauzia Maylani; Rizki Revashandi Ihsan Laduni; Binti Azizatunnafi'ah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The establishment of the Women's Empowerment Learning Center Program (PUTARAN) certainly requires a driver or main actor and supporting actors who are the implementers. With the involvement of the main actors and supporting actors, it will cause interaction in realizing the Women's Empowerment Learning Center (PUTARAN) program. This research was compiled with the aim of knowing the role of the main actors in making policies for the Women's Empowerment Learning Center (PUTARAN) program and knowing the interaction between the main actors and supporting actors in realizing it, in order to achieve the fulfillment of the rights of women online motorcycle taxi drivers and people with disabilities in Surabaya City. This research uses a qualitative method with a descriptive approach through interview techniques. This research uses Actor Network Theory according to Callon (1986) which has four groupings, such as problematization, interessement, enrollment, and mobilization. It shows that both in terms of roles and relationships between the main actors and supporting actors interact well, this can be seen from the success of the Women's Empowerment Learning Center Program (PUTARAN) which has been realized in accordance with its duties and functions.